A Conceptual Business Model Framework for Strategy and Value Addition: A Case Study of a Middleware Firm - Sim, Boon Seong (2007)
The traditional business model frameworks and concepts have been mainly used in the field of Information System (IS) and e-commerce for explanatory and descriptive purposes. I believe that there is a potential for the business model concept to be expanded for use by general businesses in strategic management. In this report, I will outline a conceptual framework for building a visual mapping of a business model. The conceptual model is a hybrid of two frameworks with the purpose of being used as a strategic tool for gaining new insight and value addition for any business. The model will be illustrated by a case study of a firm offering Massively Multiplayer Online Game (MMOG) middleware solutions for the online games industry.